The relationship between organizational culture and employees’ loyalty / Nur Qhairunnisa Wahab - Wahab, Nur Qhairunnisa (Faculty of Business and Management, 2019)
The research objective is to examine whether organizational culture which include bureaucratic culture, innovative culture and supportive culture have a positive relationship on employees’ loyalty. The target respondents are staffs who are working at Majlis Perbandaran Seremban (MPS). The quantitative research approach was adopted using five point likert scale questionnaire and the data collection managed to achieve a percentage of 85.33 percent which is 128 questionnaires returned which was derived from a total of 150 questionnaires. The collected data will be analyse using Statistical Package for Social Science (SPSS) software. This research engaged convenience sampling technique. Descriptive analysis, reliability analysis, Pearson correlation analysis and multiple regression will be used to analyse the collected data. The result shows that bureaucratic culture, innovative culture and supportive culture has positive and significant relationship with employees’ loyalty. Future researchers are recommended to focused on other sector such as private or business sector to explore more and better studies on employees’ loyalty based on the organizational culture.